2015
DOI: 10.1097/jcn.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Acute Care Nurse Practitioner and 30-Day Readmission

Abstract: The addition of a cardiac acute care NP to medical teams caring for myocardial infarction and heart failure patients had a positive impact on 30-day emergency department return and hospital readmission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 20 publications
1
45
1
6
Order By: Relevance
“…We also had no data on the effect of ACS nurse roles on patient outcomes, but other studies have documented the impact of nursing roles on outcomes (David, Britting, & Dalton, ; Johnson et al., ; Mehta et al., ; Smallwood, ). Patients with STEMI, NSTEMI and heart failure in the USA admitted to coronary care by a team that included a cardiac advanced practice nurse (CAPN) had 30‐day re‐hospitalization rates 50% lower than those admitted by a team without the CAPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also had no data on the effect of ACS nurse roles on patient outcomes, but other studies have documented the impact of nursing roles on outcomes (David, Britting, & Dalton, ; Johnson et al., ; Mehta et al., ; Smallwood, ). Patients with STEMI, NSTEMI and heart failure in the USA admitted to coronary care by a team that included a cardiac advanced practice nurse (CAPN) had 30‐day re‐hospitalization rates 50% lower than those admitted by a team without the CAPN.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 185 patients (78% NSTEMI) were not randomised, there were no significant differences by demographics, clinical characteristics or interventions between the groups. The better outcomes were attributed to the continuity provided by the CAPN, relationships built with multi‐professional teams in acute and community services, expertise developed and the teaching and family support provided by the CAPN (David et al., ). Other studies have found greater NSTEMI patient satisfaction with information when a specialist nurse was involved and greater adherence to guideline‐based care (Johnson et al., ; Mehta et al., ; Smallwood, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, programs that aim to reliably enhance access to postdischarge care and augment self‐care are among the most effective in reducing 30‐day readmissions . This includes transitional programs that leverage advanced health care professionals, such as nurse practitioners (NPs) . We aimed to pilot an NP‐driven program focusing on increased access to outpatient care in the post‐LT discharge setting and to evaluate its impact on 30‐ and 90‐day hospital readmissions.…”
mentioning
confidence: 99%
“…(9) This includes transitional programs that leverage advanced health care professionals, such as nurse practitioners (NPs). (10)(11)(12) We aimed to pilot an NP-driven program focusing on increased access to outpatient care in the post-LT discharge setting and to evaluate its impact on 30-and 90-day hospital readmissions.…”
mentioning
confidence: 99%